Dispersed habitat and its impact on land use transformation around the city of San Ramon, Costa Rica - Quesada, Marvin (Geografares, 2021)
It is investigated for four decades how the dispersed rural areas and the intermediate city of San Ramón have been transforming the use of land. One of the ways to assess the dynamics of land use changes is through photointerpretation, satellite image analysis and fieldwork. It is intended to test the hypothesis that there is an increase in urbanization and migrations, in the city of San Ramón and in the nearest district capitals, which has caused a change in land use. It was found that in the area under study as the years (decades) go by there have been gradual changes between land uses. This shows that there was a decrease between 1979 and 2019 of 30.8 % in forests, while urban areas increased by 22.0%, being the use with the largest increase. In addition, it shows how the city of San Ramón has become a polarizing axis of rural districts.